Caveolae, Caveolins, Cavins, and Endothelial Cell Function: New Insights - Sowa, Grzegorz (Frontiers in Physiology, 2012)
Caveolae are cholesterol and glycosphingolipid-rich flask-shaped invaginations of the plasma membrane which are particularly abundant in vascular endothelium and present in all other cell types of the cardiovascular system, including vascular smooth muscle cells, macrophages, cardiac myocytes, and fibroblasts. Caveolins and the more recently discovered cavins are the major protein components of caveolae. When caveolae were discovered, their functional role was believed to be limited to transport across the endothelial cell barrier. Since then, however, a large body of evidence has accumulated, suggesting that these microdomains are very important in regulating many other important endothelial cell functions, mostly due to their ability to concentrate and compartmentalize various signaling molecules. Over the course of several years, multiple studies involving knockout mouse and small interfering RNA approaches have considerably enhanced our understanding of the role of caveolae and caveolin-1 in regulating many cardiovascular functions. New findings have been reported implicating other caveolar protein components in endothelial cell signaling and function, such as the understudied caveolin-2 and newly discovered cavin proteins. The aim of this review is to focus primarily on molecular and cellular aspects of the role of caveolae, caveolins, and cavins in endothelial cell signaling and function. In addition, where appropriate, the possible implications for the cardiovascular and pulmonary physiology and pathophysiology will be discussed.